2021
DOI: 10.1093/infdis/jiab151
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Being Overweight and Obesity in People Living With Human Immunodeficiency Virus on Antiretroviral Therapy: Socioclinical, Inflammation, and Metabolic Markers

Abstract: Objectives We investigated the association between socio-clinical, inflammatory, and metabolic markers and weight gain in people with HIV (PWH) on combination antiretroviral therapy (cART). Methods Individuals from the COPANA cohort of normal weight (body mass index (BMI) of 18.5-24.9 kg/m 2) at cART initiation who achieved virological suppression (viral load <50 cp/mL) and maintained it through 36 months (M36) of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The mean BMI in our research was 20.02 ± 3.1 in men and 19.01 ± 2.6 in women. Similar results were demonstrated by the researchers from France -22.1 [16]. However, a significantly higher BMI (40.2) was demonstrated in a study conducted in Australia [17].…”
Section: Heightsupporting
confidence: 87%
“…The mean BMI in our research was 20.02 ± 3.1 in men and 19.01 ± 2.6 in women. Similar results were demonstrated by the researchers from France -22.1 [16]. However, a significantly higher BMI (40.2) was demonstrated in a study conducted in Australia [17].…”
Section: Heightsupporting
confidence: 87%
“…Weight gain is multifactorial (Goupil de Bouillé et al, 2021); factors associated with it, and with elevated body weight in HCV co-infected PLHW need to be identified in order to prevent their deleterious consequences. Studies in other populations have found that cannabis use is a potential modifiable protective factor for weight gain and elevated body weight (Alshaarawy & Anthony, 2019;Clark, Jones, Hall, Tabner, & Kmiec, 2018;Meier, Pardini, Beardslee, & Matthews, 2019).…”
Section: Introductionmentioning
confidence: 99%